In this case, we'll have to carry out several steps to find the solution.
Step 01:
data:
point 01 (-3 , 4)
point 02 (5 , 2)
Step 02:
equation of the line:
slope:
![m\text{ =}(y2-y1)/(x2-x1)=(2-4)/(5-(-3))=(-2)/(5+3)=(-2)/(8)=(-1)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/phnbe1nzwdoz7vyfeydwi55hhe5i6vkvgt.png)
Point-slope form of the line:
(y - y1) = m (x - x1)
(y - 4) = -1 / 4 (x - (-3))
(y - 4) = -1 /4 (x + 3)
![\begin{gathered} y\text{ - 4 =}(-1)/(4)x-(3)/(4) \\ \\ y\text{ = }(-1)/(4)x\text{ -}(3)/(4)+4 \\ \\ y\text{ = }(-1)/(4)x+(13)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w8cml8lwtbh9exxrwih1gtoog1zsy2t4lx.png)
The answer is:
![y=(-1)/(4)x+(13)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/e7wv5mwpuqauaxspmbmhmxsixhuotxesyv.png)